Waist-to-height ratio and its association with TV viewing in a sample of Portuguese children aged 7–9 years - Machado-Rodrigues, Aristides M.; Valente-dos-Santos, João; Fernandes, Romulo [UNESP]; Gama, Augusta; Mourao, Isabel; Nogueira, Helena; Marques, Vitor; Padez, Cristina (Wiley, 2017)
INTRODUCTION: During the past decades, increased TV viewing and reduced physical activity (PA) levels may have contributed to the increased prevalence of pediatric obesity. This study aimed to analyze the association between TV viewing and central adiposity risk in Portuguese children. METHODS: The sample comprised 3987 children (1997 girls and 1990 boys) aged 7–9 years. Height, weight, and waist circumference (WC) were measured. Waist-to-height ratio (WHtR) was calculated as the ratio of waist/height with a cut-off of 0.5 used to define risk of abdominal obesity. WHtR does not depend on sex- or age-specific reference criteria. TV viewing and PA were assessed by questionnaire. Logistic regressions were used, with adjustments for age, PA, and parental education. RESULTS: This study revealed a positive significant association between central adiposity risk and sedentary behaviors in Portuguese boys. In addition, the final model showed an important inverse association between PA and the risk of abdominal obesity in both boys and girls (males: β = −0.01 95% CI, 0.99 to 1.00; females: β = −0.01; 95% CI, 0.99-1.00). CONCLUSION: Findings revealed that associations between TV viewing and obesity risk could be highly influenced by socioeconomic factors. Future research should extend a similar design to children in other geographic contexts, and incorporate other behavioral variables in the statistical models, to confirm or not some of the aforementioned findings.